Analisis Persepsi Keislaman Remaja Melalui Konten Youtube “Belajar Islam Pake Logika” Ft Ustadz Felix Siauw - Pratama, Wahyu Saputra; Alfarizi, Zaki; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This research analyzes the perception of adolescents' Islamic perceptions through the YouTube content “Belajar Islam Pake Logika” Ustadz Felix Siauw. In the digital era, YouTube is an important tool for teenagers to learn religion. to learn religion. This research uses descriptive qualitative method with a content analysis design to understand how Ustadz Felix Siauw's rhetorical strategy influences the perception of religion. Felix Siauw's rhetorical strategy influences teenagers' Islamic perceptions. The results showed that Ustadz Felix Siauw uses logic (logos), emotion (pathos), and credibility (ethos) in conveying Islamic teachings. credibility (ethos) in conveying Islamic teachings. This approach is effective attracts teenagers, but also risks simplifying the concept of religion. This research emphasizes the importance of a balance between rational and spiritual approaches in digital da'wah so that the message remains authoritative and holistic. This research contributes to understanding the effectiveness of digital communication strategies that are relevant to the younger generation.